A case of fulminant mixed cryoglobulinemia developing after atrial myxoma resection - Mimori, Akio; Suzuki, Teruhiko; Takeishi, Michio; Arai, Eiichi; Adachi, Daisuke (Japanese Journal of Clinical Immunology, 2001)
A 63-year-old man, with a 13-year history of asymptomatic proteinuria, was diagnosed with left atrial myxoma at the onset of heart failure. After resection of the tumor by hypothermal surgery, the patient developed fever, renal failure and skin rash. The diagnosis was type II mixed cryoglobulinemia accompanied by an IgMλ clone with high titers of rheumatoid factor activity and polyclonal IgG. Treatment with high doses of steroids and plasmapheresis was ineffective, and the patient died of colon necrosis due to thrombotic occlusion in the supra-mesenteric arteries. Although the patient had suffered from sporadic Raynaud's phenomenon and purpura of the lower extremities from the age of 60 years, cryoglobulinemia was not suspected before surgery because of the atrial myxoma. Thus, we suggest that it is important to perform laboratory tests for cryoproteins before hypothermal surgery.